FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN PERSALINAN SECTIO CAESAREA TANPA INDIKASI PADA IBU POSTPARTUM DI RSUD ARIFIN ACHMAD PROVINSI RIAU TAHUN 2019 - Endang Mayasari (Universitas Pahlawan Tuanku Tambusai, 2019)
In 2007 an estimated 15% of births worldwide occurred with SC surgery. In developing countries, the proportion of births by cesarean is around 21.1% of the total births, while in developed countries only 2%. The purpose of this study was to determine the factors associated with the selection of SC deliveries without indication in postpartum mothers at Arifin Achmad Regional Hospital in Riau Province. This type of research uses a quantitative analytical research design with cross sectional study design. Case sampling technique used random sampling with a total sample of 70 people. The results showed that 40 respondents (57.14%) did not deliver SC. Respondents who delivered SC were 30 people (42.86%). There is a significant relationship between parity and SC delivery with p value = 0.00 (Î± 0.05). There is a significant relationship between age and SC delivery with p value = 0,000 (Î±